2011
DOI: 10.1007/s11517-011-0796-1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of gastric slow wave from finger photoplethysmographic signal using radial basis function neural network

Abstract: Extraction of extra-cardiac information from photoplethysmography (PPG) signal is a challenging research problem with significant clinical applications. In this study, radial basis function neural network (RBFNN) is used to reconstruct the gastric myoelectric activity (GMA) slow wave from finger PPG signal. Finger PPG and GMA (measured using Electrogastrogram, EGG) signals were acquired simultaneously at the sampling rate of 100 Hz from ten healthy subjects. Discrete wavelet transform (DWT) was used to extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This finding is in good agreement with previous work by Yacin et al (2011) which showed a strong relationship between gastric activity and systemic LFOs in the periphery. Yacin was able to reconstruct the gastric slow wave signal from a fingertip photoplethysmogram, using a deep learning approach.…”
Section: Potential Causes Of the Low Frequency Oscillationsupporting
confidence: 94%
“…This finding is in good agreement with previous work by Yacin et al (2011) which showed a strong relationship between gastric activity and systemic LFOs in the periphery. Yacin was able to reconstruct the gastric slow wave signal from a fingertip photoplethysmogram, using a deep learning approach.…”
Section: Potential Causes Of the Low Frequency Oscillationsupporting
confidence: 94%
“…An earlier review article proposed the concept of systematic low-frequency oscillations (sLFOs), which are defined as a vasogenic low-frequency BOLD signal travelling through the brain (Tong et al, 2015). It appears that the oscillation originated outside the brain (Frederick and Tong, n.d.; Li et al, 2018; Tong and Frederick, 2010) and could be caused by vasomotion (Hundley et al, 1988; Mayhew et al, 1996; Rivadulla et al, 2011), heart-rate variability (Thayer et al, 2012), respiratory volume variability (Birn et al, 2006; Chang et al, 2009), gastric oscillations (Mohamed Yacin et al, 2011; Rebollo et al, 2018) and variations in carbon dioxide levels (Sassaroli et al, 2012; Wise et al, 2004). Furthermore, previous studies using near-infrared spectroscopy have shown that such oscillations travel through the vasculature, and that strong and vascular-specific spatial structures can be captured in the macrovasculature by regressing finger-tip oxygenation time courses with the whole-brain BOLD signal (Frederick et al, 2013; Tong et al, 2015, 2014, 2011a, 2011b, 2011c; Tong and Frederick, 2014, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These sLFOs permeate the brain volume, being particularly pronounced in the vasculature. The most commonly referenced contributors to the sLFOs would be vasomotion (Hundley et al, 1988; Mayhew et al, 1996; Rivadulla et al, 2011), heart rate (Thayer et al, 2012), respiratory volume variability (Birn et al, 2006; Chang et al, 2009), gastric oscillations (Mohamed Yacin et al, 2011; Rebollo et al, 2018) and variations in carbon dioxide levels (Sassaroli et al, 2012; Wise et al, 2004). Notably, previous observations of robust anti-correlations between arterial and venous BOLD signals in the low-frequency range (Tong et al, 2019b) demonstrated the contribution of arterial BOLD to the rs-fMRI correlational structure, overturning the long-held belief that arterial BOLD effects are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks are more and more widely used in medical sciences [ 37 , 42 , 45 , 54 , 60 ]. In cardiology, they are used, inter alia, to assess the status of cardiovascular system [ 43 ], to predict the risk of coronary heart disease [ 35 ] in ECG analysis [ 36 , 56 ] or echocardiography [ 59 ].…”
Section: Discussionmentioning
confidence: 99%